Quartet repertoire for horn : Full score - COFIELD, Frank D. (Rubank Inc., 1947)
Bittersweet....Clair W. johnsonnCanon.........Mozart-GowernCarol fantasy, A.........Arr. by Harold L. WaltersnFrom A forest glen ............Paul KoepkenLegend, A...........Tschaikowsky-Irons